Biomechanics in ski jumping: A review - Schwameder, H.; Müller, E. (European Journal of Sport Science, 2001)
Biomechanical research in ski jumping has a long tradition and is determined by the work of a few important research groups. Biomechanical studies proceed nearly exclusively within three large areas (a) field studies of hill jumps, (b) laboratory studies of simulation jumps, and (c) computer simulation of the flight phase. The two main purposes of field studies of hill jumps are the description of motion and the determination of parameters relating to performance. Kinematic, kinetic, and electromyographic methods as well as computer simulation of the flight phase are used to answer these questions. Simulation jumps, primarily employed in technique-specific training, are also used for performance diagnostics. The different boundary conditions between hill and simulation jumps, however, have to be considered. The majority of computer simulations presented in the literature pursue the purpose of determining the dependence of jump distance on flight position or, respectively, on the transition from take-off to flight. Biomechanics assume an important position in the context of research of ski jumping. Further investigations should deal with questions of performance, technique-specific training, material and equipment, hill profiles, loading on the musculo-skeletal system, and prevention of injuries.